Empowerment of the Healthy Village Program through Self-Screening Management of Non-Communicable Diseases in Bogorejo Village, Merakurak District - miftahul munir; surotul ilmiyah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Introduction: Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, cardiovascular diseases, and stroke represent major public health challenges due to their increasing prevalence and long-term health impacts. Early detection through routine health screening is an important strategy to reduce the risk and complications of these diseases. However, community awareness regarding early detection of NCDs remains limited, particularly in rural areas. Methods: This community service program was conducted on February 7, 2025, in Bogorejo Village, Merakurak District, Tuban Regency, involving 50 participants consisting of community members and local health cadres. The program used a community empowerment approach through health education, training sessions, and practical demonstrations of self-screening techniques. Participants were trained to measure blood pressure, calculate body mass index (BMI), and measure waist circumference as simple indicators for early detection of NCD risk factors. Results: The results showed an improvement in participants’ knowledge and awareness regarding the importance of early detection and prevention of non-communicable diseases. Participants also demonstrated increased confidence and ability to perform simple health screening independently after receiving training and practical guidance. Discussion: Community-based education and practical training proved to be effective strategies in improving public awareness and capacity for early detection of NCDs. The involvement of local health cadres further supported community participation and contributed to the sustainability of health monitoring activities within the Healthy Village program.